Synthesis and in vitro evaluation of thermosensitive hydrogel scaffolds based on (PNIPAAm-PCL-PEG-PCL-PNIPAAm)/Gelatin and (PCL-PEG-PCL)/Gelatin for use in cartilage tissue engineering. Issue 10 (3rd July 2018) - saghebasl, Solmaz; Davaran, Soodabeh; Rahbarghazi, Reza; Montaseri, Azadeh; Salehi, Roya; Ramazani, Ali
Abstract: Background : Biodegradable thermosensitive hydrogel scaffolds based on novel three-block PCL-PEG-PCL and penta block PNIPAAm-PCL-PEG-PCL-PNIPAAm copolymers blended with gelatin were prepared and examined on functional behavior of chondrocytes.Methods : In this work, we compared two different thermosensitive hydrogel scaffolds (PNIPAAm-PCL-PEG-PCL-PNIPAAm)/Gelatin and (PCL-PEG-PCL)/Gelatin prepared by TIPS (thermally induced phase separation) method. The feature of copolymers was characterized by FT-IR, 1 H NMR. The lower critical solution temperatures (LCSTs) of aqueous solutions of copolymers were measured by cloud point (turbidity) measurements. We also examined water absorption capacity and swelling ratio. Mechanical features of the prepared hydrogels were evaluated by stress-strain measurements. Thereafter, isolated chondrocytes were cultured on each scaffold for a period of 10 days and cell arrangement and morphology studied pre-and post-plating. Cell survival assay was done by using MTT assay. The transcription level of genes Sox-9, Collagen-II, COMP, MMP-13 and oligomeric matrix protein was monitored by real-time PCR assay. The samples were also stained by Toluidine blue method to monitor the synthesis of proteoglycan.Results : Data demonstrated an increased survival rate in cells coated seeded on scaffolds, especially (PNIPAAm-PCL-PEG-PCL-PNIPAAm)/Gelatin as compared to control cells on the plastic surface. (PNIPAAm-PCL-PEG-PCL-PNIPAAm)/Gelatin had potential to increase the expression of genes Sox-6, Collagen-II, COMP and after 10 days in vitro .Conclusion : Thermosensitive PCEC/Gel and (PNIPAAm-PCEC-PNIPAAm)/Gel hydrogel scaffolds that fabricated by TIPS method possesses useful hydrophilic properties for growth and cell embedding and secretion of extracellular matrix. It can serve as an ideal strategy to promote the formation of cartilage tissue.